Two-dimensional antigenic dendrogram and phylogenetic tree of avian influenza virus H5N1 - Lai, Alexander C.K. (2012)
The hemagglutination-inhibition (HI) titers of a panel of twenty-five mouse monoclonal antibodies (MAbs) against forty-four isolates of highly pathogenic avian influenza virus H5N1 were determined. A two-dimensional antigenic dendrogram was constructed by hierarchical clustering of HI titers. Viruses with similar reactivity patterns were clustered horizontally, whereas MAbs were clustered vertically. In this 2-D dendrogram, with 40% similarity as a cut-off, four virus clusters and four MAbs clusters were identified. A phylogenetic tree based on the deduced amino acid sequence of the hemagglutinin (HA) gene of tested viruses was constructed and its topology was compared to the antigenic dendrogram. Interestingly, viruses with high genetic homology in the phylogenetic tree also had high similarity in their reactivity patterns, as indicated by their relatedness in the tree and close clustering in the dendrogram, respectively. However, the reverse and the converse were also true. Of the five pairs of viruses in the dendrogram with bootstrap values higher than 75, four pairs were in concordance with their genetic relatedness. However, one pair contained viruses belong to two distinct genetic clades. These results were discussed in the context of antigenic variation, genetic polymorphism, and the potential application of MAbs in antigenic analysis.